PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN TEMATIK MUATAN SBDP KELAS V DI SDN 82 TOKINJONG - Akhmad, Mawadda Warahma; Danial; Hardianti; Islamia, Nur; Haq, Dziaul (Universitas Islam Ahmad dahlan, 2023)
The purpose of this study is to find out the thematic learning process for class V at SDN 82 Tokinjong and what is the role of the teacher when teaching, and finally, what motivation does the teacher give to students, this research is qualitative in nature, data collection techniques use observation, interviews, and the research subject was a class V teacher as well as the principal at SDN 82 Tokinjong. Data analysis techniques in the form of data reduction, and data presentation, as well as drawing conclusions. The results of this study indicate that: The teacher's role in the thematic subjects of SBDP content plays a role in making lesson plans, methods, evaluation of learning, but there are several other teacher roles such as motivators, mediators, and evaluators in the thematic learning process that have not been implemented too much so that it has not been implemented efficiently and effectively, in terms of motivating the teacher is still not very motivating students, this can be seen when before the teacher starts the thematic learning process of SBDP content the teacher immediately applies the lecture method and does not provide motivation or in the form of support, the teacher also has not implemented an open attitude to some of his students during the learning process took place, and also the teacher had not implemented some of his roles in motivating his students to be more active during the SBDP thematic learning process that was taking place.